Anisocoria and mydriasis after scalp nerve block: a case report. Issue 5 (May 2022) - Xiao, Cheng; Chen, Fang; Tan, Yuting; Bao, Xiaohang; Jing, Sheng
Strategies for the assessment of abnormal neurological findings during general anesthesia are limited. However, pupil abnormalities may represent serious neurological complications. We herein present a case of new-onset anisocoria and mydriasis that developed after scalp nerve block. The patient's signs were possibly related to increased intracranial pressure with resulting brain shift that ultimately affected the oculomotor nerves. A 45-year-old man was scheduled for left cerebellar tumor resection and ventricular drainage surgery; however, anisocoria and left pupillary mydriasis were observed after induction of general anesthesia and performance of scalp nerve block. After reducing the intracranial pressure, the right pupil showed constriction (1 mm) but the left pupil was dilated (5 mm). The pupils were of similar size postoperatively. Although pupillary dilation during general anesthesia has been previously described, this is the first case in which the mydriasis was considered to have been caused by brain shift due to increased intracranial pressure after scalp nerve block. Thus, we propose this phenomenon as a new possible cause of pupillary changes. Actively monitoring this presentation intraoperatively could enable early detection of and intervention for complications, therefore improving the prognosis.